The Church of Our Lady at Dordrecht (Bulletin KNOB, 1989)
The Church of Our Lady at Dordrecht, one of the largest Dutch churches with a length of 106 m, is a three-aisled cross-basilica with side and radiating chapels, a tower on the west side and a large Maria chapel on the northern side of the choir. As can be read in the irregularities of the plan and in the differences of elevation and construction its building was determined by several phases. Records and the discovery of al large format bricks in the substructure of the Maria-choir were reason to date this church as built in the 12th and I3th centuries. The charter with mention of a ‘capella noviter constructa' was essential to ascertain the construction of the Church of Our Lady round 1120.Conclusions about the tower, the completion and consecration of the choir Mariachoir and cemetery could be drawn from the 'Stadsrekeningen' 1284-1297. As stated in f.e. the 'Statuten van het Kapittel' the extension with a new choir and choir chapels nearly coincides with the raised status of the Church of Our Lady to Kapittelkerk (1366- 67).Increasing building activities round 1400 could be concluded from proofs of donations and the recruitment of many craftsmen at that time. Activities on the tower are only mentioned from 1439 on, when the well-known city-architect Evert Spoorwater from Antwerpen was appointed 'Master of the Masonry'. Spoorwater played an important role at the restoration of the church after the city fire (29 june 1457), whereby only the tower, side chapels of the nave, transept and Maria-choir could be saved. At the new built parts his influence is clearly visible in the 'Brabantse' style of construction and articulation of the wall with columns and shafts, consisting of octagonal basement and cabbage leaf capitals.According to regulations concerning graves and altars in the Maria-choir at least this part of the church was in 1463-64 ready for liturgical use again. During the most recent restoration of the church (1983-87) research has however brought to light new facts with regard to her building history. The tuff walls, which were found in some of the grave cellars below the choir belong to the vaulted choir-apse of a Romanesque church (the 'capella noviter constructa'), extended later on with a tower, transept and choir. Because of changed demands the old parish church was demolished in 1366.According to the records both choir and Maria-choir of the new church must have been completed before the end of the 14th century. The drastic changes at the rebuilding of the choir as to plan, elevation and style date from after the fire (1457) and are also readable in the discovered building traces in the transept. The same new style of the columns and horizontal articulation of the wall with triforium had been applied in the middle nave.The older construction (without bunt-lines) of the roof in the eastern part of the church corresponds with the building news about the Maria-choir (1463-64). As to their details and construction the vaults in nave and transept must have been completed ca. 1500. In this way research has defined the Church of Our Lady as built on the remainders of a 12th century Romanesque church. Large building campaigns started in the second half of the 14th century. Radical changes have been carried out after the fire of 1457.